The Elements of Emotional Design Needs for Cantonese-Style Chairs - Yongjun, Ye; Azahari, Mustaffa Halabi Bin (South Asian Journal of Social Sciences and Humanities, 2025)
This study aims to explore the elements of emotional design needs of young consumers for Cantonese-style chairs, revealing their design preferences and emotional resonance within the context of modern consumption. Through semi-structured interviews with 30 young consumers aged 18 to 35, data analysis was conducted using grounded theory’s three-level coding, resulting in the identification of three core categories and their corresponding emotional demand dimensions. The findings indicate that the emotional needs of young consumers for Cantonese-style chairs primarily manifest in three aspects: appearance appeal, pleasure of use, and emotional value reflection. Specifically, appearance appeal encompasses dimensions such as the chair’s form, color, material, decoration, and structure; pleasure of use emphasizes functional practicality, ease of use, comfort, and safety and reliability; emotional value reflection includes personal, social, and co-creation emotional values. These findings provide theoretical support and practical guidance for the emotional design of Cantonese-style chairs, promoting innovation and development in the design of traditional Cantonese-style chairs.